Determinant factors of cyberbullying behaviour among Indonesian adolescents - Baidi Bukhori; Nadya Ariyani Hasanah Nuriyyatiningrum; Khairani Zikrinawati; Andrian Liem; Abdul Wahib; Darmu’in (International Journal of Adolescence and Youth)
This study aims to examine 1) the effect of religiosity, conformity, and authoritarian parenting on self-control; and 2) the effect of religiosity, conformity, and authoritarian parenting on adolescent cyberbullying behaviour, either directly or indirectly through self-control. Participants were 2,763 high school students (Mage = 16 years, SD = 0.95). The majority were from rural areas (65.5%), females (76.7%), and Muslims (98.8%). Path analysis found religiosity, conformity, and authoritarian parenting have direct effects on cyberbullying and indirect effect via self-control. Religiosity and conformity could be protective factors against adolescent cyberbullying behaviour, and conversely, authoritarian parenting could be promotive to adolescent cyberbullying behaviour. Self-control that could be strengthened through religiosity and group-conformity and weakened by authoritarian parenting, could prevent adolescents from engaging in cyberbullying behaviour.